Pentingnya Pemahaman Mengenai Gastroenteritis Akut oleh Ibu di Daerah Keramas Kelurahan Parit Culum Sabak Barat Tanjung Jabung Timur - Armina Armina; Dwi Kartika Pebrianti; Tuhu Perwitasari (Jurnal Abdimas Kesehatan (JAK), 2023)
Acute Gastroenteritis (GEA) or diarrhea is still the main cause of morbidity in children in developing countries. The main cause of death in GEA is severe dehydration as a result of fluid and electrolyte salts in diarrheal stools and loss of zinc with the stool. GEA cases are also quite high in East Tanjung Jabung Regency based on BPS data for 2020, namely 3980 cases including GEA sufferers in children aged 0 months to 14 years as many as 174 cases based on January to 14 years. May 2020. The purpose of Community Service in the Keramas area, Parit Culum Village 1 Muara Sabak Barat, is that the condition of the area is close to a murky river and water sources do not mix with the river flow so there is a need for education about the risks resulting from less clean water sources such as GEA. Service activities are carried out from March to July 2022. The method of service is carried out in the form of counseling, demonstrations of hand washing, making salt sugar/ORS, and giving leaflets. As a result of the dedication, 10 enthusiastic mothers were present in the service, 3 mothers actively asked questions, 7 mothers were able to answer back the education delivered and all mothers could demonstrate together washing hands. The results of this community service are expected to increase awareness, especially mothers in teaching and reminding children to wash their hands diligently to prevent GEA and prevent severe dehydration due to GEA.